Kewajiban Ayah Menafkahi Anak Setelah Putusnya Perkawinan - Nadia Rizkiah Latupono; Barzah Latupono; Sabri Fataruba (PATTIMURA Law Study Review, 2023)
ABSTRACT: Article 45 states that "both parents are obliged to care for and educate their children as well as possible". Paragraph (2) states "the obligations of the parents referred to in paragraph (1) of this article apply until the child marries or can stand alone, which obligations continue even if the marriage between the two parents is broken up". So in detail the rights and obligations of the parents towards children namely Providing protection, Providing education, Representing children in all legal actions for those who are eighteen years old and under and have never been married, Providing child care costs even though the parents' powers have been revoked. legal consequences arising from ex-husbands not providing maintenance to children, that can be done through the stages, summoning ex-husbands to fulfill the obligation to provide maintenance to children based on a judge's decision, forced efforts from the Court against ex-husbands to provide Hadhanah maintenance for their children. The purposes of this study are: To know and explain the obligations of fathers in providing for children after divorce, Knowing and explaining what are the legal remedies if a father is negligent in carrying out the obligation to provide for his children. The method used in this research is normative juridical. And using a statutory approach as well as a conceptual approach, with legal materials consisting of primary, secondary and tertiary legal materials which are analyzed qualitatively. The results obtained from this study are that if the ex-husband is negligent in carrying out the obligation to provide for children, that is, the ex-wife can submit a request to the Head of the District Court or the Head of the Religious Court depending on what law you use when divorcing, if Islamically it can be filed through the Religious Court, and other than Islam can be filed through the District Court.